Antibacterial activity and Phytochemical analysis of Cardanthera difformis Druce leaf extracts from West Bengal, India. - Dulal Chandra Das,; Somnath De,; Shubhankar Bhattacharya,; Monalisa Das, (International Journal of Phytomedicine, 2013)
In rural and backward areas of west Bengal of India several plants are commonly used as herbal medicine for the treatment of infectious diseases without any phytochemical and biological information in detail. The current study was to investigate the antibacterial activity and phytochemical analysis of the leaf extracts of Cardanthera difformis. Methanol, ethanol, chloroform, acetone and petroleum ether extracts of shed dried plant leaves of Cardanthera difformis were tested for antibacterial activity and phytochemical screening.The antibacterial behaviour of different extracts (methanol, acetone, ethanol, chloroform and petroleum ether) of leaves of Cardanthera difformis using the standard well diffusion assay were investigated against the seven strains of bacterial species, viz., Enterobactor faecalis, Eschirichia coli, Klebsiella pneumonia, Pseudomonous aerusinosa, Salmonella typhi, Shiegella dysentriae and Staphylococcus aureus.. Among the various solvent extract the acetone leaf extract exhibit the best antibacterial property followed by chloroform, ethanol, methanol and petroleum ether. The ethanol extract showed significant activity against Staphylococcus aureus, Pseudomonous aeruginosa, Enterobactor faecalis and Shiegella dysentriae. The acetone extract showed the highest magnitude of inhibition against Salmonella typhi among the extracts under study. Phytochemical screening of the leaf extracts using standard qualitative methods revealed the presence of saponins, flavonoids, terpenoids, tannins, quinone, carbohydrates and amino acids. Both the petroleum ether and methanol extracts showed the maximum efficiency for biochemical constituents. The present study experimentally proved the justification of traditional use of C.difformis for the treatment of various diseases and reported for the first time in the world to focus the antibacterial activity of leaf extracts of C.difformis and may lead to the development of a new generation of drugs having both chemotherapeutic and chemo preventive properties in future.